451 A systematic review exploring cultural competence in pharmacy education. (13th April 2023) - Jarrar, R; Rathbone, A P; Richardson, C; Naqvi, A A; Lim, R; Lau, W M
Abstract: Introduction: There is an increased need for a healthcare workforce that is culturally competent to improve health outcomes and reduce health disparities for patients from diverse cultural backgrounds. This is important in the context of pharmaceutical care for patients, as the inability to recognise a patient's health beliefs, which could be influenced by their cultural background, can lead to reduced medication adherence and poor treatment outcomes (1, 2). This review is registered with PROSPERO (Reference number CRD42021295875). Aim: This systematic review aims to explore cultural competence teaching and training in pre-qualification pharmacy education. Methods: This study is reported using the PRISMA Checklist. Medline, Scopus, PsychInfo, Web of Knowledge, CINAHL, and Embase databases were systematically searched for studies that explored cultural competence in pharmacy education and were published in English from January 2012 to December 2021. Methodological quality of studies were assessed using the Mixed Methods Appraisal Tool (MMAT). Data from included studies were thematically analysed. Results: Overall, 47 papers (46 studies) were included in the review. Of these, 40 papers focused on interventions for teaching cultural competence to pharmacy students only, the remaining studies included students from pharmacy and other health discipline programmes. Half of the studies focused on cultural competence in general (n = 20, 50%), while the remaining studies focused on competence on specific aspects e.g. cultures, religions and disabilities. Most studies (n = 24, 60%) report implementation of interventions that took place over a week. Twenty-one studies reported that cultural competence interventions were compulsory. There were variations in how cultural competence is conceptualised in studies; some studies focused on the need to increase knowledge about different cultures or 'knowing how'; other studies focused on behavioural aspects that would help students while they work with patients from diverse backgrounds, or 'showing how'; some studies described cultural competence as a continuum that includes both 'doing' knowledge and behavioural aspects. Conclusion: There is variation in how cultural competence is taught in pharmacy education programmes, which could be a consequence of differences in how authors conceptualised cultural competence. It is also challenging to know whether or not current interventions improve 'cultural competency' due a range of outcome measures used in the studies. Therefore, it is important to develop a set of key principles that underpin the understanding and operationalisation of the concept of cultural competence into the pre-qualification pharmacy curricula – this forms our future work. A limitation of the study was the inclusion of only papers written in English, which may therefore have inadvertently excluded relevant papers published in other languages. Additionally, grey literature was not included, which often is a key step in the dissemination of pedagogical research and scholarship. References: 1. O'Connell MB, Korner EJ, Rickles NM, Sias JJ. Cultural competence in health care and its implications for pharmacy. Part 1. Overview of key concepts in multicultural health care. Pharmacotherapy. 2007;27(7):1062-79. 2. Henderson S, Horne M, Hills R, Kendall E. Cultural competence in healthcare in the community: A concept analysis. Health Soc Care Community. 2018;26(4):590-603.